2019
DOI: 10.5539/jas.v11n7p130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Breeding Densities and Inclusion of Soybean Oil on Performance, Carcass Trait and Heat Loss in Meat Quails

Abstract: Quails are homeothermic animals, in countries with a tropical climate, such as Brazil, birds face great difficulties in controlling body temperature inside the sheds. Several practices are being studied in order to keep these animals within the thermal comfort zone, and thus, to minimize the effects of thermal stress, partial substitution of carbohydrates by oils and changes in density are some of them. The objective of this study was to evaluate the different breeding densities and inclusion levels of soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Santos et al 3 inform that diets with 3050 kcal of ME/kg increment the abdominal fat deposition of the carcasses of domestic meat quails. While Lima et al 5 did not observe an increase in abdominal fat in domestic meat quail fed 2950 kcal of ME/kg.…”
Section: Introductionmentioning
confidence: 81%
“…Santos et al 3 inform that diets with 3050 kcal of ME/kg increment the abdominal fat deposition of the carcasses of domestic meat quails. While Lima et al 5 did not observe an increase in abdominal fat in domestic meat quail fed 2950 kcal of ME/kg.…”
Section: Introductionmentioning
confidence: 81%
“…In this scenario, the infrared thermography can provide important information on the ambience of the load. The thermal imaging obtained give the possibility of target surface temperature mapping (Souza-Junior et al 2019;Rocha et al 2019;Lima et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This fluctuation is due not only to the presence of undesirable physiological changes, but also to the physical activity performed by the organism and the influence of the surrounding climatic conditions [14]. Previous studies also confirmed that IRT is an effective tool for detecting body temperature of the livestock and their parts, including hooves, susceptible to a range of diseases manifested at different stages, especially lameness [15,16].…”
Section: Introductionmentioning
confidence: 99%